Climate change, technology and intellectual property rights: Context and recent negotiations - Martin Khor (South Centre, 2012)
The new research paper discusses on contexts and recent negotiations in Technology Transfer, Sustainable Development and Climate Change. In terms of proprietary rights, the author categories technologies and related products into three domains: the Public Technologies; Patented Technologies and Future Technologies. After revealing the Effects of Patents on Access to Climate-Related Technologies, a number of measures are discussed to address problems arising should patents become a barrier to the transfer of climate related technologies.Furthermore, analyses draw on Proposals of Developing Countries in the UNFCCC; the IPR Issue & Establishment of a Technology Mechanism at the Cancun Conference of Parties (2010) and after; and the Treatment of Subsidies.
Keywords: 300